Application of Indigenous Plants for the Management of Menstruation Disorders in Orogun, Delta State, Nigeria - Erhenhi, A.H. (Sokoto Journal of Medical Laboratory Science)
Medicinal plants used for menstruation problem in Orogun town, Delta State were investigated. Some information on the indigenous uses of plants and local names obtained was provided by local indigenes of the community while the scientific information was obtained from relevant scientific literatures. Identification of the collected plant species was done in situ. A total of twenty (20) plant species were collected belonging to eighteen (17) families. The plant habits included a total of ten (10) herbs, five (5) shrubs, two (2) trees and three (3) climbers. It was evidenced from the medicinal uses that most of the plants are essential as they possess salient medicinal values in the treatment of irregular menstruation, painful menstruation, shortage of menstrual flow and black menstruation. The uses of these plants in the treatment of menstrual problems do not exclude the facts that some of the plants have multipurpose usage. While herbs were mostly used, the climbers were least used. The leaves were the most frequently used parts of the plants while the roots were least used. It is recommended that these plants of immense medicinal potentials should be conserved, cultivated or domesticated to protect them from over exploitation, hence reduce biodiversity loss or complete extinction.